(3TQM JdNjU GdeaJGMs - (3GdJaJGRGfj, SYO GdOjf, eSYhO Hf YeQ Hf YHO Gddg, J (B793 (3g`s ((3Ydj Hf ZdGe Ydj GdNhFjs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3Cf UGMH GdcTGa bO UQM HCf ajg CjVG OdGdI Ydi GNJUGU GdMeO dg hCfg Hg Mbjb hHgPG jXgQ eG PgH Edjg ef Cjf GdcdGe aj GdMeO(B...s
(3BNQgG (B:s
... (3hdG jbhe ebGeg ZjQg hgPG eYfi bhdg jXgQ (B.. (3eY GdJPcQ deG JbOe ef GdCUhd GdePchQI aj Gdafhf GdKdGKI hJaGUjd Pdc eedG dG Jaj HgG GdOaGJQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\219s
(3cTa GdXfhf (B1\473s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdHdGZIs